"Translated, it is: …" — An Ethics of Transreading. Issue 5 (October 2014) - Zhang, Huiwen (Helen)
Abstract Inspired by Friedrich Nietzsche's idea of philology and William Gass's concept of transreading, Huiwen (Helen) Zhang employs "transreader" to suggest the integration of four roles in one: reader, translator, writer, and scholar. "Transreader" recognizes that close reading, literary translation, creative writing, and cultural hermeneutics are interdependent activities with intertwined goals: to transfer, transvalue, transform, and transcend the canon. From this perspective, Lu Xun, China's Nietzsche, is a twentieth‐century transreader of the canon, and his prose poem "Revenge (The Second)" delivers a self‐referential ethics of transreading. Zhang's transreading of this poem shows why slow reading is today more necessary than ever, in what sense translation is a universal dilemma, how humanity grows when its expression grows more subtle, and that transreading opens a space for genuine communication.